AAMP is a binding partner of costimulatory human B7-H3. Issue 1 (30th June 2022) - Ciprut, Sara; Berberich, Anne; Knoll, Maximilian; Pusch, Stefan; Hoffmann, Dirk; Furkel, Jennifer; Gahlawat, Aoife Ward; Kahlert-Konzelamnn, Lena; Sahm, Felix; Warnken, Uwe; Winter, Martin; Schnölzer, Martina; et al.
Abstract: Background: Targeted immunotherapies are of growing interest in the treatment of various cancers. B7-H3, a member of the co-stimulatory/-inhibitory B7-family, exerts immunosuppressive and pro-tumorigenic functions in various cancer types and is under evaluation in ongoing clinical trials. Unfortunately, interaction partner(s) remain unknown which restricts the druggability. Methods: Aiming to identify potential binding partner(s) of B7-H3, a Yeast two-hybrid and a mass spectrometry screen were performed. Potential candidates were evaluated by bimolecular fluorescence complementation (BiFC) assay, co-immunoprecipitation (Co-IP), and functionally in a 3 H-thymidine proliferation assay of Jurkat cells, a T-cell lineage cell line. Prognostic value of AAMP and B7-H3 expression was evaluated in IDH1wt GBM patients from the TCGA-GBM cohort. Results: Of the screening candidates, CD164, AAMP, PTPRA, and SLAMF7 could be substantiated via BiFC. AAMP binding could be further confirmed via co-IP and on a functional level. AAMP was ubiquitously expressed in glioma cells, immune cells, and glioma tissue, but did not correlate with glioma grade. Finally, an interaction between AAMP and B7-H3 could be observed on expression level, hinting towards a combined synergistic effect. Conclusion: AAMP was identified as a novel interaction partner of B7-H3, opening new possibilities to create a targeted therapy against the pro-tumorigenic costimulatory protein B7-H3.